Narrativas da mobilidade: comunicação, cultura e produção em espaços informacionais - Camila Maciel Campolina Alves Mantovani (2011)
This research stems from the issue of the mobility phenomenon, through the pathway tread by subjects in need of connection and access to uninterrupted information flow. In this informational, cultural and technological context, the presence of mobile dispositives stands out, especially cell phones. Such artifacts, which contain not only voice services, but texting information, and Internet connections, are increasingly present in urban settings, changing access, production, and dissemination of information. Therefore, with the paradigm of mobility and its connections to globalization theories and information societies, the research aimed to capture the role of information and mobile technologies in the constitution of the contemporary mobility pattern. Therefore, the study sought to identify and characterize the defining elements of the mobility era through information flows from three main instances: the academic discourse surrounding the phenomenon, the dispositive and its technical, cultural and economic dimensions, and narratives of subjects who make use of such dispositives. The strength of the symbolic construction of a connected society that is available for interactive processes stands out among the results. Therefore, those who make use of mobile, incorporating it to the different activities inherent in their routine, establish new ways of being in the world, situated between the real and the virtual movement. However, despite distinct motivations for the movement and transit within specific mobility contexts, there are regularities in these behaviors and in the perception of mobility. The connection made possible with the use of mobile technologies becomes one of the most significant aspects of mobility for informational flows: connections are established for entertainment, work, study, location, retail, and expression of feelings. The information processes resulting from the interaction possibilities and mobility implemented by mobile technology become increasingly complex and establish new paradigms for production, access, and dissemination of current information. This demands a broader view of what the era of mobility and connection is and what its demands are for continuous flow of information.